2011
DOI: 10.1016/j.jbi.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Taiwanese method for providing patients data from multiple hospital EHR systems

Abstract: Personal Health Record (PHR) systems are growing in popularity and are receiving increased attention from the Biomedical Informatics research community. Information Collection is one PHR research topic and includes system functionality that helps patients retrieve their data from external sources. One of the most potentially useful external sources of information is the data stored in patients' EHRs at medical institutions. PHR systems that support Information Collection from EHR systems are thus interesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Information will be updated from the reception desk when the patients are discharged or after outpatient visit from the participating hospitals. The overall design architecture is presented in our other paper [9]. In this paper a general concept of the design is presented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information will be updated from the reception desk when the patients are discharged or after outpatient visit from the participating hospitals. The overall design architecture is presented in our other paper [9]. In this paper a general concept of the design is presented.…”
Section: Methodsmentioning
confidence: 99%
“…TMT is a local electronic record template that has been developed by adopting international standards such as HL7 Clinical Document Architecture (CDA), which is supposed to provide interoperability within healthcare systems [8]. The present research is centered on a USB-based Health Records project that promises to develop a fully interoperable and portable PHR system in Taiwan [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Results of this study showed that data exchange and data sharing methods are issues that could be mentioned in transferring data. Media like USBs, mobiles or data repositories store and keep data and exchange them among the care spectrum using the Internet and online or offline databanks between various service providers (17, 18, 24), while another study recommended presenting data to patients using USBs (31). In a study under the title of “Telehomecare and Reducing Healthcare Expenditures”, Noel et al installed a monitor in patients’ homes for the supervision of nurses in the central station and provided the connection between patient and care provider via video conference.…”
Section: Discussionmentioning
confidence: 99%
“…With electronic transfer systems, personal health records or transfer documents are electronically recorded in apps or electronic health records (Jian et al . , Nazi et al . ).…”
Section: Discussionmentioning
confidence: 99%